Beyond the Pandemic: Transforming Food Systems after COVID-19 - Swinnen, Johan (2021)
Johan Swinnen GLOBAL FOOD POLICY REPORT Transforming Food Systems after COVID-19: Implications of the 2021 Global Food Policy Report for Eurasia Co-Organized by the Eurasian Center for Food Security at Lomonosov Moscow State University, Westminster International University in Tashkent, Armenian National Agrarian University, the World Bank, & IFPRI MAY 27, 2021 - 07:30 AM TO 09:00 AM EDT